TANTANGAN PENGEMBANGAN PADI DIKABUPATEN KEPULAUAN MENTAWAI - Azhari, Rafnel; Rusman, Bujang; Kasim, Musliar; Syarif, Auzar; Reflinaldon, Reflinaldon; Yasin, Syafrimen; Zainal, Afrizal; Junaidi, Junaidi (Jurnal AGRISEP, 2017)
This study aims to identify the problems and develop rice agribusiness in Mentawai Islands from upstream to downstream and formulate appropriate policy recommendations to be implemented. The research location determined by purposive namely in the village Makalo and Malakopa District of South Pagai, Sikakap subdistrict Taikako Village, Village Saumanganya District of North Pagai, Bosua Village and Village Beriulou District of South Sipora, Village Rogdog and Madobag District of South Siberut. Respondents in this study were 30 farmers. Respondents farmers selected by simple random sampling method. The results showed that the majority of rice paddies new openings in six districts consist of peatlands with a depth varying from 0.4- > 2.0 meter, fields new openings that have been implemented in the Mentawai Islands in general can not be expected to result in maximum productivity due to problems of land suitability diverse. Farmers also do not take action appropriate technical culture starting from land preparation, seed selection, weeding, fertilizing and water management. Behaviorally agriculture, farmers in Mentawai Islands is not a society that blends with the culture of rice fields, it is because basically their agricultural base is dry land agriculture with farming patterns. This will certainly give a great challenge and not easy for the cultivation of rice in the Mentawai Islands.